Integrasi Rencana Strategis dan Pengukuran Kinerja Menggunakan Kerangka Teori Strategic Performance Management dengan Pendekatan Soft Systems Methodology - Haji, Rusno (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This paper examines integration process of strategic plan and performance measurement in Research Development and Training Agency, Ministry of Religion Affairs using Strategic Performance Management theoretical framework with Soft Systems Methodology. Based on the comparison between the conceptual models with problem situations in the real world, the problem solving interest generated some recommendations regarding the structure, processes and attitudes. Meanwhile, for research interest, it is concluded that the theoretical framework of Strategic Performance Management can be used to integrate the strategic plan and performance measurement in the public sector, because it can answering problem complexity, supporting the integration of long-term strategy process, and operational objectives, ensuring the performance measurement support thestrategic and organization learning achievement, as well as improving theintegration and data analysis and facilitating cooperation and collaboration.